Opportunities for nurses to support recovery after pediatric injury: Relationships among posttraumatic stress, hope, and quality of life. Issue 1 (13th February 2019) - Weiss, Danielle; Ostrowski‐Delahanty, Sarah; Van Allen, Jason; Seegan, Paige; Marsac, Meghan L.
Abstract: Purpose: Nurses are at the forefront of children's postinjury recovery; this unique role provides an opportunity for nurses to recognize and screen for symptoms that may interfere with children's quality of life (QOL). As such, aims of the present investigation were to explore selected variables (e.g., posttraumatic stress symptoms [PTSS], hope) that have the potential to impact QOL after pediatric injury, with a larger goal of contributing to recommendations for nursing practice to support children's full (physical and emotional) recovery during the peritrauma period following injury. Design and methods: Sixty children (aged 7–13) completed measures of PTSS, hope, and QOL while receiving injury treatment. Results: PTSS significantly predicted concurrent QOL, β = −0.42, p  = 0.001. Exploratory results demonstrated that specific PTSS clusters (re‐experiencing [ β = −0.39; p  = 0.003), avoidance [ β = −0.35; p  = 0.009], arousal [ β = −0.34; p  = .012]) all significantly predicted QOL. Specific PTSS were explored. Hope (overall, domains of pathways, general agency, goal setting) did not significantly predict concurrent QOL. Practice implications: While this study is exploratory and more research is needed, current results suggest that nurses' awareness of PTSS (including symptoms of re‐experiencing, avoidance, arousal) may help medical teams in identifying children that are at risk for impaired functional recovery (e.g., QOL) during the peritrauma period. Nurses may want to consider advocating for the integration of PTSS screeners into standard medical care. In addition, nurses have the opportunity to serve as key medical professionals in the delivery of trauma‐informed medical care (which aims to minimize further trauma or re‐traumatization). Nursing leadership may want to consider offering training in how nurses can identify and respond to children who have experienced an injury (such as trauma‐informed care).